2021
DOI: 10.1051/medsci/2020280
|View full text |Cite
|
Sign up to set email alerts
|

Nociception, douleur et autisme

Abstract: Les sujets autistes présentent fréquemment des anomalies sensorielles. Celles concernant la nociception ainsi que sa potentielle résultante, la douleur, sont d’un intérêt capital. En effet, du fait de nombreuses comorbidités, les sujets autistes sont plus souvent exposés à des situations douloureuses que la population générale. Alors qu’ils sont souvent considérés comme moins sensibles, les études expérimentales sur ce point sont loin de faire consensus. Utiliser des modèles animaux pourrait permettre de s’aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Several studies have assessed the perception of acute pain in autistic patients [ 16 , 17 ] and suggest that their perception of pain is normal but expressed differently. In their literature review, Ruelle-Le Glaunec et al [ 18 ] describe multiple studies on populations with autism spectrum disorders, reporting either hypersensitivity, hyposensitivity, or normal sensitivity to acute pain. This demonstrates the lack of consensus regarding the issue of painful perception in patients with autism spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the perception of acute pain in autistic patients [ 16 , 17 ] and suggest that their perception of pain is normal but expressed differently. In their literature review, Ruelle-Le Glaunec et al [ 18 ] describe multiple studies on populations with autism spectrum disorders, reporting either hypersensitivity, hyposensitivity, or normal sensitivity to acute pain. This demonstrates the lack of consensus regarding the issue of painful perception in patients with autism spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The DSM-V [10] also includes hypersensitivity and hyposensitivity in its definition. While many authors have focused on the question of acute pain [16][17][18], very few delve into the issue of chronic pain in patients with autism spectrum disorders. Patients with chronic pain are regularly excluded from studies on painful perception [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that people with ASD often exhibit abnormal somatic or cutaneous sensations (Asmika et al., 2018 ; Ben‐Sasson et al., 2009 ), and many observational studies have shown patients with ASD have difficulties in atypical pain perception, expression, and pain assessment (Bogdanova et al., 2022 ; Moore, 2015 ; Ruelle‐Le Glaunec et al., 2021 ; Vaughan et al., 2020 ). However, skin is the most widely distributed and earliest developing sensory organ in the human body.…”
Section: Introductionmentioning
confidence: 99%